Proceso contable de bienes de larga duración del Gobierno Provincial de los Ríos - Robles Sánchez, Olinda Geovana (2017)
Fixed Assets are those Long-lived Articles with a Purpose Determined By Both Their Physical Form (In The Case Of The Tangibles), And By The Special Rights They Own (In The Case Of The Intangibles); This work is related to the accounting process of long-term assets of the Provincial Government of Los Ríos The Investigation Process Of This Case Study Has Been Considered Laws, Agreements, Regulations And Regulations Updated, Issued By The Different Organizations Oriented To The Management And Control Of Fixed Assets In The Public Sector. They have also used investigative techniques related to the line of research that is the management of accounting information, for having consistency with the records and documents related to accounting; However, in addition to this is also part of the financial management of a way and social commitment, since closely related to assets that provide care to citizens, but not seek economic profitability. In the Autonomous Decentralized Provincial Government of Los Ríos, Criteria are set for the recognition, capitalization, valuation, reduction and control of long-lived assets. However, Criteria are not established when there is loss of these. In this Prestigious Institution, One Of The Largest Of The Province Of The Rivers, There Are Serious Drawbacks Related To The Accounting Of Long-Term Goods; In the majority of cases due to lack of knowledge about the good management of the assets that it owns and for not having structured standardized process flows, that allows a better management and control of the indicated assets.